Development of a Pulsed Laser Ablation Technique for the Formation of Carbon Nanotubes - Beh, Hoe Guan (2006)
The objective of this work was to develop a pulsed laser ablation technique for the formation of carbon nanotubes (CNTs). This study was divided into three parts. The first part involved the development of pulsed laser ablation (PLA) system. The second part dealt with the growth of CNTs by using the pulsed laser ablation technique, and finally the last part dealt with the analysis of microstructure and surface morphology of the deposited sample collected and the influence of the laser ablation on the surface morphology of the sample target. A vacuum chamber was designed for the formation of CNTs. The stainless steel chamber used in this system has a cylindrical shape, with diameter of about 15cm and 45cm length. CNTs were formed by laser ab!ation using a graphite pellet, graphite-Ni, graphite-Co and graphite-Ni-Co, each with 10 weight percentage catalysts. The Nd:YAG laser with 532nrn wavelength, 10.24 W laser power was used to ablate the target to form the CNTs. Argon (Ar) gas was kept flowing into the chamber, keeping the pressure inside chamber at 4 Torr.Web-liked CNTs were found in the deposited sample collected after 30 minutes laser ablation by using the graphite pellet and the graphite filled with mono-catalyst and bi-catalyst. The XRD pattern for the deposited sample shows the CNTs peak located at about 26.5". The SEM micrograph show that the diameter size of the CNTs formed by the Co, Ni, NiCo catalysts and without catalyst follow the order C>CCo>CNi>CNiCo. The range of the diameters of the CNTs was found to be about 35-150nm. The sphere-liked carbon structures were found deposited in the substrate after laser ablation without the Ar gas flowing into the chamber during the ablation process. TEM micrograph confirmed the formation of CNTs. It was found that by using a bi-metal catalyst (Ni-Co), a bamboo-like structure of CNTs was formed.